Realizing Intrinsically Ultralow and Glass‐Like Thermal Transport via Chemical Bonding Engineering - Zhonghao Xia; Xingchen Shen; Jun Zhou; Yuling Huang; Yali Yang; Jiangang He; Yi Xia (Advanced Science)
Abstract Crystals exhibiting glass‐like and low lattice thermal conductivity (κL) are not only scientifically intriguing but also practically valuable in various applications, including thermal barrier coatings, thermoelectric energy conversion, and thermal management. However, such unusual κL are typically observed only in compounds containing heavy elements, with large unit cells, or at high temperatures. In this study, chemical bonding principles are utilized to weaken the Ag–Ag bonds and enhance lattice anharmonicity. The incorporation of a chalcogen anion as a bridge ligand is proposed to facilitate phonon rattling in Ag6‐octahedron‐based compounds. Guided by this design strategy, five Ag6 octahedron‐based compounds, AAg3X2 (A = Li, Na, and K; X = S and Se), which are characterized by low average atomic masses and exhibit exceptionally strong four‐phonon scattering, are theoretically identified. Consequently, these compounds demonstrate ultralow thermal conductivities (0.3–0.6 W m−1 K−1) with minimal temperature dependence (T−0.1) across a wide temperature range. Experimental validation confirms that the κL of NaAg3S2 is 0.45 W m−1 K−1 within the temperature range of 200–550 K. The results clearly demonstrate that weak chemical bonding plays a crucial role in designing compounds with glass‐like κL, highlighting the effectiveness of chemical bonding engineering in achieving desired thermal transport properties.